Morphological characteristics and mitochondrial COI gene of the green water dragon in Phu Quoc island, Vietnam - Van Thong Ngo; Huu Hanh Tran; Chi Tao Phan (Vietnam Journal of Science, Technology and Engineering, 2021)
The green water dragons of Phu Quoc island, Vietnam have been given a VU rating (vulnerable) by the Vietnam red data book and the International Union for conservation of nature and natural resources. A description of the morphological characteristics and sequenced mitochondrial cytochrome oxidase subunit 1 COI gene was completed following a survey of thirty individuals from September 2018 to May 2019. Their body weights ranged from 115 to 850 g and their snout-vent length ranged from 120 to 280 mm. They were identified to have the highest similarity to the species Physignathus cocincinus by the barcode of life data system. Their COI gene sequence was compared to GenBank (KM272197.1) and the following alternations were found: C5483T, A5486C, C5537A, A5564G, A5591G, T5633C, G5684A, A5771G, A5849C, C5927T, T5942C, C5993T, G6002A, and A6020G. The neighbourjoining tree of their COI sequence divergence indicated a distance (compared to the same published species) from 2.3 to 2.8%. Thus, it might be possible that the green water dragons of Phu Quoc island are evolving into a specific subspecies. However, more green water dragon specimens from Phu Quoc should be sequenced to ensure a conclusion and further research into farming should be initiated to protect this vulnerable species